2023
DOI: 10.1145/3568671
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Seismic Sensor based Target Detection, Localization, Identification, and Activity Recognition

Abstract: Current sensor technologies facilitate device-free and non-invasive monitoring of target activities and infrastructures to ensure a safe and inhabitable environment. Device-free techniques for sensing the surrounding environment are an emerging area of research where a target does not need to carry or attach any device to provide information about its motion or the surrounding environment. Consequently, there has been an increasing interest in device-free sensing. Seismic sensors are extremely effective tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The study analyzed numerous articles related to EEG signal processing, identified limitations, and analyzed future development trends. Besides biomedical and BdM fields, the role of signal processing in ML has been addressed in various fields such as audio analysis and recognition [14]- [20], seismic signal analysis [20]- [22], and telecommunications [23]- [30].…”
Section: Introductionmentioning
confidence: 99%
“…The study analyzed numerous articles related to EEG signal processing, identified limitations, and analyzed future development trends. Besides biomedical and BdM fields, the role of signal processing in ML has been addressed in various fields such as audio analysis and recognition [14]- [20], seismic signal analysis [20]- [22], and telecommunications [23]- [30].…”
Section: Introductionmentioning
confidence: 99%
“…Their frequency band must cover 0.01 to 100 Hz and ground motions from 1 nm to 10 mm [ 18 ]. From classical seismic receivers placed at or close to a designated area [ 19 ] to downhole receivers immersed at typical depths [ 20 ] or to latest optical fiber network enhancing [ 21 ], seismic sensors detect certain ground vibrations with the highest precision and process the information in real-time to trigger an alert. Lately, seismic recording instruments have gained particular importance in assisting the monitoring processes of other natural phenomena, such as rainfall episodes or thunderstorms [ 22 ], or for target detection and activity recognition [ 23 ].…”
Section: Introductionmentioning
confidence: 99%